1991
DOI: 10.1002/jbmr.5650061423
|View full text |Cite
|
Sign up to set email alerts
|

Journal of Bone and Mineral Research

Abstract: In 1969, a health survey was offered to all inhabitants of a town district in Sweden. A clinical examination was carried out, and among other variables, a measurement was made of serum calcium. The same procedure was repeated in 1971. From these two investigations a cohort of 176 individuals (1.1%) with sustained hypercalcemia was identified who could be followed during the subsequent 15 years. Comparisons were made with an age- and sex-matched control group from the same health survey. Survival was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…One explanation for these incongruent mortality data is that more patients in the American studies (7,8) had mild disease, with lower serum calcium levels and fewer symptoms, than patients in the European studies (2)(3)(4)(5)(6), where average calcium levels were significantly higher. This hypothesis is supported by data from Nilsson et al (9) who analyzed mortality over a 30-yr period in 10,995 Swedish patients who underwent parathyroidectomy.…”
Section: Mortalitymentioning
confidence: 79%
See 1 more Smart Citation
“…One explanation for these incongruent mortality data is that more patients in the American studies (7,8) had mild disease, with lower serum calcium levels and fewer symptoms, than patients in the European studies (2)(3)(4)(5)(6), where average calcium levels were significantly higher. This hypothesis is supported by data from Nilsson et al (9) who analyzed mortality over a 30-yr period in 10,995 Swedish patients who underwent parathyroidectomy.…”
Section: Mortalitymentioning
confidence: 79%
“…The increase in cardiovascular mortality in patients with severe and moderately severe PHPT has been well documented in studies from Scandinavia (2)(3)(4)(5). The higher mortality rate declines with time from parathyroidectomy, but persists long after surgical cure, suggesting that PHPT may cause enduring damage to the cardiovascular system (6).…”
Section: Mortalitymentioning
confidence: 95%
“…The increase in cardiovascular mortality in patients with severe and moderately severe PHPT has been well documented in studies from Scandinavia (31)(32)(33)(34)(35). The higher mortality rate declines with time from PTX, but persists long after surgical cure, suggesting that PHPT may cause enduring damage to the cardiovascular system (36).…”
Section: Mortalitymentioning
confidence: 92%
“…One explanation for these incongruent mortality data is that more patients in the American studies (37,38) had milder disease, with lower serum calcium levels and fewer symptoms than patients in the European studies (31)(32)(33)(34)36). This hypothesis is supported by a Swedish study investigating mortality over a 30 year time period in 10,995 patients who underwent PTX (39).…”
Section: Mortalitymentioning
confidence: 99%
“…Patients continue to have a residual excess risk of mortality after parathyroidectomy although younger patients and those with milder PHPT more quickly return to the normal survival curve [35,36]. Population based studies in Sweden have demonstrated excess long-term mortality in ''asymptomatic'' unoperated patients [37][38][39][40]. The Swedish population studies have shown that patients with PHPT have 1.5-fold higher relative mortality compared to controls.…”
Section: Mortality Of Phptmentioning
confidence: 98%